"Killing two birds with one stone" - a qualitative study on women's perspectives on the dual prevention pill in Johannesburg, South Africa - Siyanda Tenza; Lydia Mampuru; Mpho Moji; Sihle Zulu; Lorna Begg; Irene V. Bruce; Krishnaveni Reddy; Barbara A. Friedland; Thesla Palanee-Phillips; Sanyukta Mathur (BMC, 2024)
Abstract Background HIV incidence remains high in South Africa, with ~ 60% of all new HIV infections among adolescent girls and women (Country factsheets HIV and AIDS Estimates, 2022). Oral pre-exposure prophylaxis (PrEP), approved for HIV prevention in South Africa since 2015, is hampered by low uptake and adherence, particularly among adolescent girls and young women (AGYW). Combining oral PrEP with oral contraceptives could increase PrEP uptake, persistence and address unmet needs for contraception. We investigated the acceptability of a dual prevention pill (DPP), combining oral PrEP and a combined oral contraceptive (COC) for HIV and pregnancy prevention among women in Johannesburg, South Africa. Methods Between March-July 2021, we conducted 12 focus group discussions (FGDs) with adolescent girls and women (n = 74) aged 16-40 stratified by ages (16-17, 18-24, 25-40), half of whom were COC users. We explored adolescent girls and women's opinions about the DPP concept, existing HIV and pregnancy prevention options, and input on perceived facilitators and barriers to DPP use. FGDs were conducted in English or isiZulu, using a standardized interview guide. FGDs were audio-recorded, transcribed to English and analyzed using ethnographic content analysis. Results The majority viewed the DPP favorably as a multipurpose option preventing unplanned pregnancy and HIV. Most saw it as a convenient "two-in-one" solution, requiring one clinic visit for both PrEP and COCs. AGYW were viewed as the most likely to benefit from the DPP due to the likelihood of multiple partners and unplanned sex, possibly preventing school dropout from unplanned pregnancy or HIV acquisition. The DPP was perceived to be more reliable than condoms, especially when condom negotiation is limited. Benefits were also seen by participants in rape cases, protecting against pregnancy and HIV. DPP use barriers included side effect concerns, unsupportive partners and judgmental healthcare providers. Conclusions/significance The DPP was perceived as acceptable for HIV and pregnancy prevention to AGYW in Johannesburg and its dual indications helpful in supporting improved PrEP uptake and persistence. DPP implementation programs need to consider solutions to potential barriers, like education on DPP benefits, coupled with reliable side effect support and healthcare provider sensitization as part of routine sexual health services to encourage uptake and adherence.